Klausula Eksonerasi Oleh Pelaku Usaha Dalam Perjanjian Jual Beli Rumah - Wishnu Kurniawan; Ninis Nugraheni (Faculty of Law Hang Tuah University, 2017)
The exenoration clause is an exclusion / liability exclusion clause in a housing sale and purchase agreement. The purpose of writing this scientific article is to find out the accountability of business actors for offers submitted to prospective consumers and restrictions on the inclusion of standard clauses containing exenoration clauses in the offer of buying and selling houses as a legal protection effort for consumers. The results of the study indicate that the treaty law in Indonesia essentially assumes that brochures have binding legal force. This binding strength is based on the fact that the brochure is a binding form of supply as specified in the Consumer Protection Act which is based on the principle of good faith at the pre-contractual stage. Judging from the freedom of contract the standard agreement with an exoneration clause does not meet the subjective and objective requirements as specified in Article 1320 BW, thus the exoneration clause stated by the business actor in the brochure as a bidding instrument does not have binding power. Provisions for transferring accountability, actions in the form of business actors are not responsible for changes in specifications contained in brochures violating Article 18 paragraph (1) letters a, c, and d of Consumer Protection Act. And has an effect on null and void (nietig / null and void).